Apium graveolens leaf ethanolic extract triggers apoptosis in human tongue cancer cells via caspase-3 and poly(ADP-ribose) polymerase pathways: An in vitro study - Sandra, Ferry; Hartono, Tiffany; Hayuningtyas, Ria A.; Ranggaini, Dewi; Halim, Johni; Lee, Kyung H. (Narra J, 2025)
Recent advances in cancer treatment have focused on developing alternative therapies with reduced adverse effects. Chemoprevention using natural products derived from plants has gained significant attention. Apium graveolens has demonstrated anticancer properties against various cancer cell types, suggesting its potential efficacy against tongue cancer cells. The aim of this study was to evaluate the cytotoxic effects and mechanisms of action of Apium graveolens leaf ethanolic extract (AGLEE) on the HSC-3 tongue cancer cell line. The leaves were processed and extracted with 70% ethanol to obtain an ethanolic extract. HSC-3 cells were cultured, subjected to starvation, and pre-treated with or without Z-DEVD-FMK, a caspase-3 inhibitor. Subsequently, the cells were treated with or without doxorubicin or varying concentrations of AGLEE. To assess cell viability and apoptosis, MTT and sub-G1 assays were performed. Additionally, treated HSC-3 cells were collected, lysed, and analyzed for levels of cleaved-caspase-3 and cleaved-poly (ADP-ribose) polymerase (cleaved-PARP) using ELISA. The inhibitory concentration (IC50) value of AGLEE for reducing viable HSC-3 cells was determined to be 48.29 μg/mL. AGLEE significantly decreased HSC-3 cell viability and increased the percentage of apoptotic cells. It exhibited a concentration-dependent reduction in cell viability and an increase in apoptosis. Furthermore, the extract elevated the levels of cleaved-caspase-3 and cleaved-PARP in HSC-3 cells. Pre-treatment with Z-DEVD-FMK reduced the levels of cleaved-caspase-3 and cleaved-PARP induced by AGLEE. Taken together, AGLEE could be proposed as a potential natural therapeutic agent by inducing apoptosis through the caspase-3/PARP pathway in tongue cancer cells.